Evaluation of the PaO2/FiO2 Ratio as a Risk Factor for Hypoxemia against Septicemia Mortality in Children who Treated at Dr. Soetomo General Hospital - Yuli Astika; Arina Setyaningtyas; Dominicus Husada; Retno Asih Setyoningrum (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Severe septicemia can result in impaired oxygen perfusion to the tissues. The PaO2/FiO2 ratio(P/F ratio) is one of the measurement parameters for hypoxemia. This study aims to evaluate the P/F ratio asa risk factor for hypoxemia against septicemia mortality in children.Method: An observational with a prospective cohort design was conducted. Thirty-six patients withsepticemia, consisting of 18 patients who living (survivor) and 18 patients who died (non-survivor). TheP/F ratio is obtained based on blood gas analysis carried out in the first 24 hours of treatment recorded onmedical records and calculated manually. The P/F ratio has an area under the curve (AUC) of 0.83 (95%CI 0.71–0.95) with a cut-off of 226. Septicemia children with P/F ratio < 226 who have a mortality riskof up to 6.9 times (RR 6.9; 95% CI 1.719-27.957; p= 0.005) with sensitivity 72.70%; specificity 72.20%;PPV 76.19%; NPV 68.42%. The mean P/F ratio in the non-survivor group was significantly lower than thesurvivor group 161.60 (95% CI 1.05) compared to 391.09 (95% CI 2.13); p= 0.005).Conclusion: The P/F ratio can be a risk factor for hypoxemia on septicemia mortality.